Functional Wnt Signaling Is Increased in Idiopathic Pulmonary Fibrosis - Königshoff, Melanie (Public Library of Science, 2008)
BACKGROUND: Idiopathic pulmonary fibrosis (IPF) is a fatal lung disease, characterized by distorted lung architecture and loss of respiratory function. Alveolar epithelial cell injury and hyperplasia, enhanced extracellular matrix deposition, and (myo)fibroblast activation are features of IPF. Wnt/β-catenin signaling has been shown to determine epithelial cell fate during development. As aberrant reactivation of developmental signaling pathways has been suggested to contribute to IPF pathogenesis, we hypothesized that Wnt/β-catenin signaling is activated in epithelial cells in IPF. Thus, we quantified and localized the expression and activity of the Wnt/β-catenin pathway in IPF. METHODOLOGY/PRINCIPAL FINDINGS: The expression of Wnt1, 3a, 7b, and 10b, the Wnt receptors Fzd1-4, Lrp5-6, as well as the intracellular signal transducers Gsk-3β, β-catenin, Tcf1, 3, 4, and Lef1 was analyzed in IPF and transplant donor lungs by quantitative real-time (q)RT-PCR. Wnt1, 7b and 10b, Fzd2 and 3, β-catenin, and Lef1 expression was significantly increased in IPF. Immunohistochemical analysis localized Wnt1, Wnt3a, β-catenin, and Gsk-3β expression largely to alveolar and bronchial epithelium. This was confirmed by qRT-PCR of primary alveolar epithelial type II (ATII) cells, demonstrating a significant increase of Wnt signaling in ATII cells derived from IPF patients. In addition, Western blot analysis of phospho-Gsk-3β, phospho-Lrp6, and β-catenin, and qRT-PCR of the Wnt target genes cyclin D1, Mmp 7, or Fibronectin 1 demonstrated increased functional Wnt/β-catenin signaling in IPF compared with controls. Functional in vitro studies further revealed that Wnt ligands induced lung epithelial cell proliferation and (myo)fibroblast activation and collagen synthesis. CONCLUSIONS/SIGNIFICANCE: Our study demonstrates that the Wnt/β-catenin pathway is expressed and operative in adult lung epithelium. Increased Wnt/β-catenin signaling may be involved in epithelial cell injury and hyperplasia, as well as impaired epithelial-mesenchymal cross-talk in IPF. Thus, modification of Wnt signaling may represent a therapeutic option in IPF.